The ideals and disappointments of the “New Woman”: the image of Liza Bakhareva in the сontext of the era - Tukhtaeva, Nargiskxon (The Lingua Spectrum, 2025)
The purpose of this article is to explore the spiritual, moral, and educational aspects of the Russian national character through the lens of fiction and the portrayal of the "new woman" in the works of writers from the second half of the 19th century. The article analyzes the structural elements of female characters, such as their portraits, time spent in their parents' homes, their personalities, and their conflicts with society. The article concludes that the artistic representations of this period can be seen as a vivid reflection of the tumultuous and transformative era of the 1860s, capturing the typical patterns and individuals of that time.